2013
DOI: 10.1186/1678-9199-19-20
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of cervical adenocarcinoma cells (HeLa) to venom from the scorpion Centruroides limpidus limpidus

Abstract: BackgroundThe venom of Centruroides limpidus limpidus (Cll) is a mixture of pharmacologically active principles. The most important of these are toxic proteins that interact both selectively and specifically with different cellular targets such as ion channels. Recently, anticancer properties of the venom from other scorpion species have been described. Studies in vitro have shown that scorpion venom induces cell death, inhibits proliferation and triggers the apoptotic pathway in different cancer cell lines. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The variations in response to crude venom on growth of the four cell types after 24 h exposure might be a result of the complex composition of the venom and/or the targets expressed on cancer cells [ 12 ]. This observation is consistent with previous studies in which venoms of other scorpions such as Rhopalurus junceus , Androctonus crassicauda and Centruroides limpidus limpidus also induced selective and differential cytotoxicity against different human malignant cell lines [ 12 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The variations in response to crude venom on growth of the four cell types after 24 h exposure might be a result of the complex composition of the venom and/or the targets expressed on cancer cells [ 12 ]. This observation is consistent with previous studies in which venoms of other scorpions such as Rhopalurus junceus , Androctonus crassicauda and Centruroides limpidus limpidus also induced selective and differential cytotoxicity against different human malignant cell lines [ 12 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…This approach can hypothesize that this susceptibility differential may be related to the expression of the HeLa cell, recognized by the TsV venom. Indeed, as seen by Contreras-Ortiz and colleagues [30], venom of the scorpion Centruroides limpidus limpidus was not cytotoxic to HeLa cell cultures, suggesting that this may be partially attributable to the absence of specific cell membrane targets for molecules present in the venom.…”
Section: Discussionmentioning
confidence: 93%
“…However, the sensitivity of HeLa cells to scorpion venom may vary with the source of the venom. Contreras-Ortiz et al (33) found that the venom from the scorpion Centruroides limpidus was not detrimental to HeLa cell cultures. HeLa cells had high survival rates following exposure to the venom, which did not induce apoptosis and there was no evidence of chromatin condensation or DNA fragmentation (33).…”
Section: Discussionmentioning
confidence: 99%